Low cycle fatigue and creep-fatigue response of the 316Ti stainless steel - S.C.S.P. Kumar Krovvidi; Sunil Goyal; A. K. Bhaduri (Fracture and Structural Integrity)
SS 316Ti is widely used in bellows industry and is a good candidate material for high temperature bellows in sodium cooled fast reactor (SFR) systems. Typical operating temperature experienced by SFR systems is around 823K. Design of bellows for nuclear applications need to be in compliance with the standard design codes such as ASME section-III and RCC-MR. The fatigue data and cyclic stress strain curve of SS316Ti are not available in design codes such as RCC-MR or ASME section-III/NH. Hence, the material data required for high temperature design of bellows are generated experimentally. Initially, the basic tensile data such as yield strength, ultimate tensile strength and % elongation of the material were obtained from tensile testing at 823K. Low cycle fatigue tests were carried out in strain controlled mode on SS316Ti at 823K different strain ranges in air and variation of number of cycles with strain range was obtained. Creep-fatigue interaction (CFI) experiment was also conducted at 823K and strain amplitude of 0.4% with 1 minute hold time in peak tensile strain. The stress response (peak stress variation with number of cycles) of the material showed continuous hardening up to saturation followed by crack nucleation and final failure. The fatigue life was found to decrease with increase in strain range. The fatigue life decreased in presence of hold period in tension. The design fatigue curve for SS316Ti at 823K has been generated using the LCF data by incorporating factors of safety on strain and number of cycles. Cyclic stress strain curve was generated for the material at 823K. The tensile, LCF and CFI data generated will be useful in design of SS316Ti bellows for SFR systems.